ANALISA EFEKTIVITAS DAN EFISIENSI MENGGUNAKAN TEKNIK AUDIT MANAJEMEN PADA FUNGSI PEMASARAN (Studi Kasus Pada PT Madu Kembang Joyo Sriwijaya) - Inge Fitri Admantyasyahri (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to analyze the efficiency and effectiveness of marketing functions using management audit techniques at PT Madu Kembang Joyo Sriwijaya. Management audit in marketing function is used to monitor and determine areas of problem and current and future opportunities and to provide recommendation based on the condition of the company, so an efficient and effective marketing that can support related functions within the company is created. This case study uses descriptive method through questionnaires, interviews, and documentation. The  effectiveness and efficiency of marketing functions are analyzed and evaluated by comparing the criteria, causes, and effects and recommendation. Based on the results of research it can be concluded that, in general, the activities of marketing functions of PT Madu Kembang Joyo Siwijaya are quite effective yet not quite efficient. Therefore, PT. Madu Kembang Joyo Sriwijaya must continuously strive to improve the existing marketing functions. This study provide some recommendations and alternatives to be considered by the company to create effective and efficient marketing functions. Keywords : Management Audit, Effectiviness, Efficiency, Marketing Function